2004
DOI: 10.1128/jcm.42.8.3495-3504.2004
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Differentiation of Aspergillus Species from Other Medically Important Opportunistic Molds and Yeasts by PCR-Enzyme Immunoassay

Abstract: We developed a PCR-based assay to differentiate medically important species of Aspergillus from one another and from other opportunistic molds and yeasts by employing universal, fungus-specific primers and DNA probes in an enzyme immunoassay format (PCR-EIA). Oligonucleotide probes, directed to the internal transcribed spacer 2 region of ribosomal DNA from Aspergillus flavus, Aspergillus fumigatus, Aspergillus nidulans, Aspergillus niger, Aspergillus terreus, Aspergillus ustus, and Aspergillus versicolor, diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 73 publications
(82 reference statements)
3
36
0
Order By: Relevance
“…The good performance (sensitivity and specificity) of the present array might be due to the fact that the fungal ITS sequences have low intraspecies variation and high interspecies divergence (10,19,21,24,32). Until now, there has been no report defining the criteria for maximum intraspecies variation in the ITS regions.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The good performance (sensitivity and specificity) of the present array might be due to the fact that the fungal ITS sequences have low intraspecies variation and high interspecies divergence (10,19,21,24,32). Until now, there has been no report defining the criteria for maximum intraspecies variation in the ITS regions.…”
Section: Discussionmentioning
confidence: 98%
“…Invasive aspergillosis is a leading cause of infection among patients undergoing treatment for hematological malignancies, solid organ transplantation, and hematopoietic stem cell transplantation (8,10,37). Aspergillus fumigatus remains the most frequent cause of invasive aspergillosis, followed by A. flavus, A. terreus, A. niger, A. nidulans, and A. versicolor (12,22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, assays targeting multicopy genes have better detection limits than those targeting single copy genes. 135 Although PCR may become a diagnostic modality to identify Mucorales, [136][137][138] Scedosporium, [139][140][141] and several other fungi, [142][143][144][145][146][147][148][149][150][151] no commercial test is available to date. These techniques hold promise, but they are not yet standardised or readily available in most clinical laboratories.…”
Section: A R K E R S F O R O T H E R I N V a S I V E F U N G A L I mentioning
confidence: 99%
“…terreus is of concern. In addition, the probability to produce fulminant invasive infection in immunocompromised patients is possible (3). Numerous findings have indicated that a substantial cause of fungi found in hospitals is from potted plants (4).…”
Section: Introductionmentioning
confidence: 99%